Iffah sebagai nilai akhlak qur’ani: studi tematik surah an-nur ayat 33 - Fahmi, Layyina Af Idah (Maliki Interdisciplinary Journal, 2026)
The increasing spread of moral challenges, social interaction issues, and digital-era temptations urges Muslims to return to Qur’anic ethical values, one of which is the concept of ʻiffah. Surah An-Nūr verse 33 provides essential guidance for Muslims who are not yet able to marry, instructing them to preserve their dignity and restrain themselves from actions that lead to fornication. This study aims to examine the meaning of ʻiffah in this verse and explore its relevance in contemporary Muslim life. The research employs a qualitative descriptive method through library research, analyzing classical and contemporary tafsir sources along with modern literature on morality. The findings indicate that ʻiffah, etymologically and textually, refers to self-restraint, lowering the gaze, protecting the private parts, and avoiding all pathways leading to zina. Contemporary interpretations expand ʻiffah to include digital ethics, appropriate online interaction, and the challenges faced by today’s youth in navigating social and technological environments. This study concludes that the value of ʻiffah remains highly relevant as a moral framework that prevents social degradation and contributes to shaping a dignified, ethically grounded Muslim character.